PENGARUH PARTISIPASI ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI (Studi Empiris Pada SKPD Kabupaten Indrigiri Hulu) - Threzasyari, Yulfriza; Indrawati, Novita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The Purpose of this research is to examine : 1). The effect of budgetary participation on budgetary slack 2). The effect of budget goal clarity on budgetary slack 3). The effect of budgetary participation on budgetary slack with locus of control as moderating variable 4). The effect of budget goal clarity on budgetary slack with locus of control of moderating variable. The population on this study is Regional Working Units (SKPD) at Indragiri Hulu. This sample in this study was taken with a purposive sampling method. The sample in this studyare performance of the district unit Indragiri Hulu which amounted to 75 respondents. Data collections techniques used multiple regression analysis and moderating variable test analysis where processed using SPSS. The result of this study show that budgetary participation and budget goal clarity significant influence on budgetary slack and then variable locus of control moderate the effect of the budgetary participation and budget goal clarity on budgetary slack. The amount of influence (